Corrigendum to: The Association of Serum Vitamin D Levels with Pseudoexfoliation Glaucoma/Syndrome - Dikci, Seyhan; Öztürk, Emrah; Fırat, Penpe Gül; Yılmaz, Turgut; Taşkapan, Mehmet Çağatay; Yoloğlu, Saim (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
In the Original Article by Dikci et al. “The Association of Serum Vitamin D Levels with Pseudoexfoliation Glaucoma/ Syndrome” (Endocr Metab Immune Disord Drug Targets. 2019; 19(2):166-170) after publication of the article it has come to the corresponding author's attention that there were some errors in the article. In the introduction section, reference 3 should be changed as reference 2 (paragraph 1, line 4) and references 4-6 should be changed as references 3-6 (paragraph 1, lines 6,7). Reference numbers in the references section should be as follows. References 25-28 should be changed as references 7-10 respectively. References 7-24 should be changed as references 11-28 respectively.